Implications of Developing Fayd Al-Barakat Book on Learning Qiraat sab’ah in the Digital Era - Roni Susanto; Robbin Dayyan Yahuda; Basuki Basuki; Abdul Kadir Ahmad (STAI Hubbulwathan Duri, 2023)
The discourse of the digital era qiraat sab’ah study in Indonesia faces theoretical and practical problems. Theoretical problems are shown by the minimal number of qiraat sab’ah experts, while practical problems are evidenced by the low interest in learning qiraat sab’ah. The DITPD Pontren survey in 2021 explained that only 65 of 26,975 Islamic boarding schools in Indonesia teach qiraat sab’ah. The next survey from the National Statistics Agency in 2021 shows that only two universities in Indonesia teach qiraat sab’ah. This requires further investigation to solve theoretical and practical problems in qiraat sab’ah. This study aims to discuss the implications of developing Fayd al-barakat book on learning qiraat sab’ah in the digital era. This study uses qualitative methods to explore the genealogical aspects and development models of the Fayd al-barakat book in the digital era and its implications for learning qiraat sab’ah at Ponorogo. The data source was obtained from the manuscript of the qiraat sab’ah KH. Husein Ali and interviews with 1 Kiai, 5 ustadz, and 6 students. The method of tracing genealogical books and chain paths uses Rahman's hermeneutics. Data analysis uses content analysis methods through data reduction, data display, and conclusions. Display data using domain analysis. The results of this study showed that the development of the fayd al-barakat book at PPTQ al-Hasan Ponorogo produced a manuscript of the qiraat sab’ah book, while its implications for learning qiraat sab’ah were relevant to the characteristics and realities of the digital era society.